Perceived Public Stigma and Attitudes towards Seeking Psychological Help among Turkish and Pakistani People - Sarwat Sultan (Pakistan Journal of Psychology, 2012)
This paper reviews the comparison of perceived public stigma and their attitudes towards seeking psychological help between Turkish and Pakistani students. The sample consisted of 432 students evenly split between Pakistani (N=216) and Turkish (N=216) students. Using convenience sampling technique, the sample was recruited from Bahauddin Zakariya University, Multan – Pakistan, and Bahcesehir University, Istanbul – Turkey. Perceived Devaluation– Discrimination Scale (Link, Yang, Phelan, et al. 2004) and Attitudes towards Seeking Professional Psychological Help Scale (Fischer & Farina, 1995) were used to collect information. The findings showed that Pakistani students perceive higher stigma and report negative attitudes towards seeking psychological help than Turkish students. No gender differences were found among Turkish students while Pakistani female students were found to be higher in reporting stigma and negative attitude towards psychological help than male students. Perceived public stigma was also found negatively correlated with attitudes towards seeking help. Study suggested that educating people through mass media about the accounts of psychological ailments and treatment would enhance positive attitudes and accurate portrayals of mental illness.